Contemporary Art from the Netherlands : A selection by John Hallmark Neff, Chicago. - Hallmark Neff, John (Amsterdam : Visual Arts Office for Abroad of the Ministry for Cultural Affairs, 1982)
Akkerman, Ben ; Struycken, Peter ; Schoonhoven, Jan J. ; Visser, Carel ; van der Heyden, J.C.J. ; van de Kop, David ; Boezem, Marinus ; Gudmundsson, Sigurdur ; Mol, Pieter Laurens ; Abramovic, Marina ; Ulay ; Freijmuth, Alphons ; Holstein, Pieter ; van 't Slot, John ; Commandeur, Jan
Tentoonstelling 'Contemporary Art from the Netherlands', Museum of Contemporary Art, Chicago, March 1982.
boek